Studi Deskriptif Perilaku Cybersex Pada Remaja - Hafiva Rahma Yohana; Maya Yasmin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to look at the description of cybersex behavior in adolescents. This study used a quantitative approach involving 750 adolescents with an age range of 15-19 years. The measuring instrument used was ISST (Internet Sex Screening Test) which was compiled by the researcher based on aspects of cybersex by Delmonico and Miller (2003). The results showed that cybersex activity in this study was in the moderate category at 53.5%.